Konflik Kerja Dan Budaya Organisasi Dalam Meningkatkan Efektivitas Madrasah Aliyah - Sukatin .; Yulia Putri (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This study aims to analyze work culture management and work conflict in improving organizational effectiveness at Batang Hari 1 State Islamic Senior High School. The study employed a qualitative descriptive approach, with data collection techniques including observation, unstructured interviews, and documentation. Research informants were identified through purposive sampling, including the principal, teaching staff, and administrative staff. Data analysis was conducted using the Miles and Huberman model, comprising data reduction, data presentation, and conclusion drawing. Its validity was tested through source and technique triangulation. The results indicate that systematically planned and participatory work culture management fosters discipline, responsibility, and harmonious cooperation. The implementation of a digital attendance system and administrative streamlining enhances employee professionalism and performance. Work conflicts arising from differences in perception, workload, and adaptation to the new system can be managed constructively through open communication and a persuasive approach. Thus, a strong work culture and effective conflict management contribute significantly to increased organizational effectiveness, as reflected in the achievement of the school's vision and mission and the creation of a conducive and productive work environment.